Physician assistants in medical ward care: a descriptive study of the situation in the Netherlands. Issue 3 (23rd December 2015) - Timmermans, Marijke J. C.; van Vught, Anneke J. A. H.; Van den Berg, Michiel; Ponfoort, Erik D.; Riemens, Frank; van Unen, Jacco; Wobbes, Theo; Wensing, Michel; Laurant, Miranda G. H.
Abstract: Rationale, aims and objectives: Medical ward care has been increasingly reallocated from medical doctors (MDs) to physician assistants (PAs). Insight into their roles and tasks is limited. This study aims to provide insight into different organizational models of medical ward care, focusing on the position, tasks and responsibilities of the involved PAs and MDs. Methods: In this cross‐sectional descriptive study 34 hospital wards were included. Characteristics of the organizational models were collected from the heads of departments. We documented provider continuity by examination of work schedules. MDs and PAs in charge for medical ward care ( n  = 179) were asked to complete a questionnaire to measure workload, supervision and tasks performed. Results: We distinguished four different organizational models for ward care: medical specialists in charge of admitted patients (100% MS), medical residents in charge (100% MR), PAs in charge (100% PA), both MRs and PAs in charge (mixed PA/MR). The wards with PAs had the highest provider continuity. PAs spend relatively more time on direct patient care; MDs spend relatively more time on indirect patient care. PAs spend more hours on quality projects ( P  = 0.000), while MDs spend more time on scientific research ( P  = 0.030). Conclusion: Across different organizational models for medical ward care, we found variations in time per task, time per bed and provider continuity. Further research should focus on the impact of these differences on outcomes and efficiency of medical ward care.